Upaya Meningkatkan Motivasi Belajar Peserta Didik dalam Pembelajaran Daring Melalui Media Game Edukasi Wordwall Di Kelas IV SDN 01 Tanahbaya Tahun Pelajaran 2020/2021 - Rizki Dwi Lestari (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
The purpose of this study was to increase students' learning motivation in online learning using wordwall educational game media in grade IV SD N 01 Tanahbaya. The focus of this research is to increase students' learning motivation in online learning. This research is a Classroom Action Research using Kurt Lewin's model. The subjects in this study were the fourth grade students of SD N 01 Tanahbaya for the academic year 2020/2021 totaling 13 students. Data collection techniques using observation techniques, questionnaires and documentation. Indicators of success in research can be measured from the acquisition of a learning motivation questionnaire score which shows between 76% -100%, which is a good category. The results showed that the use of wordwall educational game media could increase students' learning motivation in online learning. This is evidenced by the increase in students' learning motivation scores before the action by 66% in the first cycle, an increase of 66% to 72%. Meanwhile, in the first cycle to the second cycle, it increased by 12% to 84% in the good category.